Reading Immigration with The Book of Unknown Americans by Cristina Henríquez - Schnee, Emily (Radical Teacher, 2018)
This Teaching Note describes using The Book of Unknown Americans by Cristina Henriquez to spark critical inquiry about immigration in developmental English and composition courses at a New York City community college.